An Analysis Of Use Uninterruptible Power Supply (UPS) On Power Consumption At Iconnet Network Transmitter Stations - Asni Ati Mutia; Amani Darma Tarigan; Beni Satria (Sean Institute, 2024)
The use of Uninterruptible Power Supply (UPS) plays a crucial role in maintaining power stability, especially in ICONNET network transmission stations, which require a reliable and uninterrupted power supply. UPS functions as a backup power source that prevents sudden power disruptions, reducing the risk of equipment damage and service interruptions in telecommunication networks. This study aims to analysed the impact of UPS usage on power consumption at ICONNET transmission stations. The research methodology includes measuring power consumption before and after UPS implementation, analysing power efficiency, and evaluating the impact of UPS on system reliability. Data were collected through monitoring electrical load, UPS operation duration, and power performance during grid outages. The results indicate that UPS usage can optimize power consumption efficiency by stabilizing voltage and frequency. Additionally, UPS contributes to enhancing the operational reliability of transmission stations by preventing downtime caused by power failures from the main grid. However, UPS efficiency is highly influenced by battery capacity, power conversion efficiency, and the electrical load characteristics of the transmission station. Thus, this study provides insights for network operators in selecting and managing appropriate UPS systems to improve energy efficiency and transmission system reliability.